Resources and potential of the native flora for fodder and sown pasture production in the arid and semi-arid zones of North Africa - Houerou, H.N. le (International Center for Arid and Semi-Arid Land Studies, 1979)
Discusses the ecology, germination, temperature, dormancy, water stress, salinity & alkalinity, water requirements, potential yields, feed value, and seed production of local fodder species used in current agricultural practice and of species which have been experimentally tested and subject to semi-large scale demonstration. Also describes briefly some species of interest.